2018
DOI: 10.1590/1518-8345.2342.2947
|View full text |Cite
|
Sign up to set email alerts
|

Labor conditions and the meanings of nursing work in Barcelona

Abstract: Objective:to analyze the relationship between the quantitative assessment of working conditions and the qualitative perception of one’s own work experience. Method:a sample of 1,760 nursing professionals from Barcelona answered a questionnaire assessing their working conditions and summarized their own current work experience in five key words. Results:the textual corpus of the meanings of nursing work included 8043 lexical forms, which were categorized and codified. Respondents who rated their work conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
7
0
8
Order By: Relevance
“…However, burnout and other psychic disorders have been the target of investigations from the perspective of working conditions analysis and detailing of the variables that permeate this construct ( 8 - 11 ) . In this sense, organizational issues in Brazilian and European Nursing work have also been reflected in the physical and mental illness of workers due to adverse working conditions aggravated by the recent economic crisis, which exposed the workers of these scenarios to increased work overload, poor dimensioning of human resources, increased informal ties and fear of unemployment ( 8 , 10 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, burnout and other psychic disorders have been the target of investigations from the perspective of working conditions analysis and detailing of the variables that permeate this construct ( 8 - 11 ) . In this sense, organizational issues in Brazilian and European Nursing work have also been reflected in the physical and mental illness of workers due to adverse working conditions aggravated by the recent economic crisis, which exposed the workers of these scenarios to increased work overload, poor dimensioning of human resources, increased informal ties and fear of unemployment ( 8 , 10 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Nursing still appears as the professional category that performs the longest working day among health care professionals (29) . A study revealed that, despite positively understanding their work as a care relationship, nursing workers recognize the deficiencies and deficits associated with the organization and working conditions -such as work overload, lack of autonomy and deficit of staff and material -, thus pointing to an ambivalent work (30) . It is important to highlight that long working days were associated with inadequate working conditions, work overload and stress (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic that emerged in the organizational dimension of professional implications was the time devoted to the development of EPS support and articulation roles. Other studies have also identified that short time, justified by a hard work routine of health professionals, represents one of the challenges for the development of EPS articulation ( 25 ) and the professional practice of nurses ( 26 - 27 ) .…”
Section: Discussionmentioning
confidence: 99%